2010
DOI: 10.3146/ps08-023.1
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic Differences in Current Peanut (Arachis hypogaea L.) Cultivars in Phenology and Stability of These Traits under Different Irrigation Scheduling Methods

Abstract: Understanding differences among peanut (Arachis hypogaea L.) cultivars in growth and phenology and the interactions with environment (G X E interactions) for these traits allows predictions for yield potential or performance in variable environments. Despite the importance of this information, very little quantitative data exists on the differences in aboveground growth, canopy architecture, and reproductive phenology for currently grown peanut cultivars. This study quantified differences in these traits among… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…3). Previosuly, Rowland et al (2010) also observed linear response of kernel weight with pod yield in regression analysis, however, noticed non-significant effect of irrigation scheduling method on any measured trait in groundnut. Further, the current study successfully demonstrated that selection based on 100-kernel weight will result in the improvement of dry pod yield of groundnut.…”
mentioning
confidence: 87%
“…3). Previosuly, Rowland et al (2010) also observed linear response of kernel weight with pod yield in regression analysis, however, noticed non-significant effect of irrigation scheduling method on any measured trait in groundnut. Further, the current study successfully demonstrated that selection based on 100-kernel weight will result in the improvement of dry pod yield of groundnut.…”
mentioning
confidence: 87%
“…Alabama, US by Davis and Mack (1991), 5.0-7.0 in Texas, US by Kiniry et al (2005), about 4.5-6.8 in Georgia, US by Rowland et al (2010), 5.1-5.3 in South China by Qi et al (2020), and 4.9-6.5 in Georgia, US by Zhang et al (2022). The observed higher CO 2 flux can be attributed to lower intra-row competition for space, light, water and nutrients in twin-row as compared to single-row peanut (Hauser and Buchanan, 1981;Wehtje et al, 1984).…”
Section: Figure 12mentioning
confidence: 98%
“…A water balance method utilizes known environmental parameters and crop growth stage to estimate soil water content. The primary water balance methods used across the USA and other international peanut‐growing regions include evaporation pans (Khan and Datta, 1982; Pahalwan and Tripathi, 1984; Rowland et al, 2010; Wright et al, 1986), Irrigator Pro (Lamb et al, 2007; Rowland et al, 2010), the University of Georgia Extension checkbook method (UGA‐EXT) (Rowland et al, 2010), MOISNUT (Davidson et al, 1998a), EXNUT (Davidson et al, 1998a,b), and AQUAMAN (Chauhan et al, 2013). Relative to producer‐derived methods or rainfed environments, water balance scheduling methods are purported to improve yield, net returns, and/or irrigation water use efficiency (IWUE) up to 50% in overhead‐irrigated environments (Chauhan et al, 2013; Davidson et al, 1998a,b).…”
Section: Useful Conversionsmentioning
confidence: 99%